Jejunal feeding: when is it the right thing to do?. Issue 5 (25th November 2019) - Paine, Peter; McMahon, Marie; Farrer, Kirstine; Overshott, Ross; Lal, Simon
Abstract : The decision to commence jejunal feeding in patients with structural abnormalities, which prevent oral or intragastric feeding, is usually straightforward. However, decisions surrounding the need for jejunal feeding can be more complex in individuals with no clear structural abnormality, but rather with foregut symptoms and pain-predominant presentations, suggesting a functional origin. This appears to be an increasing issue in polysymptomatic patients with multi-system involvement. We review the differential diagnosis together with the limitations of available functional clinical tests; symptomatic management options to avoid escalation where possible including for patients on opioids; tube feeding options where necessary; and an approach to weaning from established jejunal feeding in the context of a multidisciplinary approach to minimise iatrogenesis.